Galileo and 400 Years of Telescopic Astronomy - Grego, Peter; Mannion, David; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Imagine yourself living 400 years ago, right before the telescope was first used by Galileo to look up into the skies and find unforeseen wonders. You probably believed, with most of the known world, that Earth was at the center of the magnificent parade of planets and stars above you, and the Sun$1 (Bs purpose in journeying across the sky was to give Earth daylight and warmth. Suddenly, though, your world is turned upside down. The Church, all powerful in its doctrines and teachings of the times, continues to support theories that don$1 (Bt fit the facts presented by scientists. Scientists in their quest for truth must hide their findings or risk the harsh penalties imposed by the Church. We have gone from a comforting Earth-centered universe to a tiny floating spec in a gigantic cosmos, barely a comma in a lengthy treatise. And we have gone there in a blink of an eye. We may have lost our central position in the universe, but Grego and Mannion show us how much we have gained in understanding the universe around us. And we are only at the beginning of our journey. Their words help us to discover our place again and how we got there and what we might expect to learn in the centuries to come.s
Eyes on the Skies -- Galileo Magnifico -- Newton$1 (Bs Universe -- Surveying the Solar System -- A Bigger Picture Unfolds -- Beyond Vision.s
Keywords: Physics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy